The Influence of Safety Commitment, Implementation of SOP, Supervision and Competency on Work Accidents At PT. Haleyora Power Unit Service Pekanbaru - Maulana Yazid Al Annuri; Mohammad Riza Sutjipto; Muhammad Awaluddin (West Science Business and Management, 2023)
This research was conducted to determine the effect of Safety commitment, implementation of SOPs, supervision, and competence on work accidents at PT. Haleyora Power Unit Service Pekanbaru. The object of this research is technical service officers. This research is quantitative and descriptive. The data source in this research is primary data obtained by collecting answers from respondents through a questionnaire. The total number of respondents used was 263 employees. This research uses linear regression analysis with data processing using SPSS 26. The results of partial and simultaneous hypothesis testing show that the sig value is <0.05, which means that Safety commitment, application of SOPs, supervision, and competence influence work accidents. In the multiple value regression test, negative coefficient values were obtained for the three independent variables, which means that the higher the Safety commitment, implementation of SOPs, supervision, and competence, the smaller the number of work accidents that occur.